EN Methods for managing the energy efficiency of a reliquefaction plant operating on the reverse brighton cycle of a LNG tanker - В.В. Соколовська-єфименко; Л.І. Морозюк; В.О. Єрін; О.О. Єфименко; А.В. Мошкатюк (Holodilʹnaâ Tehnika i Tehnologiâ)
LNG is transported over long sea and ocean distances only by tankers, called LNG carriers, in large on-board tanks at a temperature of -163ºC. Although these tanks are well insulated, some of the LNG evaporates under the external factors influence, and boil-off-gas gas (BOG) is formed. The main method of dealing with BOG is the reliquefaction of LNG. Many LNG carriers use technology based on the reverse Brighton cycle (RBC) for reliquefaction. The study has been carried out by thermodynamic analysis methods of the actual parameters and characteristics of the BOG reliquefaction plant based on the data obtained during the operation of the LNG carrier “UMM AL AMAD”. Energy and entropy-statistical methods of thermodynamic analysis have been used in the research. The reliquefaction plant operation has been evaluated based on the specific compression work consumption and the value of the effectiveness of a thermodynamic cycle. The analysis of the results showed that the investigated system operating according to the Brighton cycle has low energy efficiency values. The most energy-intensive loop is the nitrogen loop. It accounts for over 90% of the work overspending in the reliquefaction plant. The expander work partially compensates for the overexpenditure of compressor work. Irreversibility in the expander is 7.7%, and the N2 compressor is approximately 48.7% of the total irreversibility of the liquefaction process. In the BOG/LNG loop, the main contribution to the processes’ irreversibility is made by the BOG compressor (~3.7%) and the precooler (~1.55%) of the total irreversibility of the liquefaction process. The cryogenic heat exchanger is a component of both loops and its negative impact is estimated at 36.4% of the total irreversibility of the liquefaction process. The application of reliquefaction plants operating on the Brighton cycle is currently inefficient due to low energy efficiency and huge losses in the nitrogen loop, which does not meet IMO requirements for gas carriers